1998
DOI: 10.1039/a707458a
|View full text |Cite
|
Sign up to set email alerts
|

Speciation of chromium in tanned leather gloves and relapse of chromium allergy from tanned leather samples†

Abstract: There are concerns that wearing chromium tanned leather gloves can provoke a lapse of hand dermatitis in chromium sensitive patients. Various forms of chromium have different biological effects and the determination of total chromium (both soluble and insoluble), which often is used in clinical studies, may therefore not be an adequate measure of the adverse exposure. However, investigations, where dissolution of hexavalent chromium from leather gloves has been experimentally studied, could not been found in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 6 publications
3
20
0
Order By: Relevance
“…Other studies have also demonstrated that a significant amount of Cr(VI) and Cr(III) is capable of leaching out of leather products (46,47,50).…”
Section: Chromium In Leather Productsmentioning
confidence: 95%
See 1 more Smart Citation
“…Other studies have also demonstrated that a significant amount of Cr(VI) and Cr(III) is capable of leaching out of leather products (46,47,50).…”
Section: Chromium In Leather Productsmentioning
confidence: 95%
“…During the tanning process, basic chromium(III) sulfate binds to the collagen thereby stabilizing the leather (45). However, even though no Cr(VI) is used, small trace amounts of Cr(VI) can often be found in leather articles (46,47). This is due to oxidation of Cr(III) during leather manufacture leading to the formation of Cr(VI).…”
Section: Chromium and Leather Tanningmentioning
confidence: 99%
“…The real tannery effluent samples were passed through 0.45 m Whatman GF/C filters, diluted and analyzed for total dissolved chromium by FAAS after an acid decomposition of the leather samples, according to general AAS procedures [32,33].…”
Section: Analysis Of the Real Tannery Wastewatermentioning
confidence: 99%
“…, and amino acids (1 g?L 21 of each amino acid) [13,25,26,27]. The amino acids selected were threonine, methionine, serine, alanine, and glycine.…”
Section: Detection Of Chromium Species After Incubation Of Simulated mentioning
confidence: 99%